Study on the workability, strength, durability and environmental performance of alkali-activated electrolytic manganese slag-fly ash-slag grouting materials - Yongquan Chen; Zhonghu Wu; Chi Zeng; Yuan Liu; Shaoyun Pu; Hui Zhang; Zheng Feng; Kun Xu; Deliang Ni (Case Studies in Construction Materials)
In engineering applications, groundwater, Cl-, SO42- and other erosive environments significantly affect the performance of grouting materials and their service life. In this work, the changes in the durability performance of manganese slag-based grouting material (EMCGM) under the erosive conditions of groundwater, a NaCl solution and a Na2SO4 solution were investigated, and the feasibility of the use of EMCGM was explored through the aspects of its basic performance, residual strength factor, toxic leaching and environmental and economic benefits. The study revealed that the compressive strength of EMCGM can reach 16.2 ∼19.3 MPa in 28d of standard maintenance, and the flexural strength can reach 5.9–7 MPa. According to the residual strength coefficient, the order of the erosion effect is as follows: NaCl solution > Na2SO4 solution > groundwater, and the main reason for the decrease in the durability performance of the samples after erosion is the dissolution of some of the hydration products and corrosion. The leaching concentration of heavy metals in EMCGM is lower than the national standard, which is in line with the environmental protection requirements. Microstructural analysis revealed that the main hydration products were C-(A)-S-H and N-A-S-H, accompanied by ettringite formation. In addition, the average cost of EMCGM is 1250 RMB/t, and the average carbon emission is 84.86 kg/t, which is significantly lower than that of other grouting materials on the market, making this material advantageous for green, low-carbon and economically efficient, applications and endowing it with broad application prospects.